PENGARUH PENGGUNAAN MODEL PBL TERHADAP MOTIVASI BELAJAR BIOLOGI SISWA KELAS X MIA - Asrorul Azizi; Irwansah Irwansah (LPPM Institut Pendidikan Nusantara Global, 2020)
ABSTRACT This research purpose to increase student learning motivation, and student learning outcomes using Problem Based Learning (PBL) model in the X class of MIA MA Darul Aminin NW Aikmual. The type of research was Classroom Action Research with descriptive methods. The subjects of this study were all students in the X class of MIA MA Darul Aminin NW Aikmual. The research procedure was carried out in two cycles, each cycle consisting of 4 stages, namely: 1) planning, 2) implementation, 3) observation 4) reflection. The variables of this research are the Problem Based Learning (PBL) model, student learning motivation and student learning outcomes. Data collection techniques in this study were observation, questionnaires and tests. The research instrument used was the observation sheet, questionnaire sheet and test sheet. The percentage of student learning motivation in the first cycle who has high motivation is 63.63% and medium category motivation is 36.36% and 0% is low category. Students' learning motivation in cycle II has increased to be 86.3% high category, 13.7% medium category and 0% low category. The attitudes learning outcome data in the first cycle was 3.59, increasing in the second cycle to 3.64. Student learning outcomes experienced learning completeness, namely in the first cycle of 64% with 14 students completed and 8 incompleted students. The analysis of student learning outcomes in cycle II experienced learning completeness which was 88% with 20 students completed and 3 incompleted students. It can be concluded that the Problem Based Learning model can improve motivation and learning outcomes in the X class of MIA MA Darul Aminin NW Aikmual.